Ostrácodos binodicopas del Ordovícico de la Precordillera de San Juan, Argentina (Ameghiniana, 2014)
Binodicope faunas from the Arenigian to early Caradocian rocks of the Precordillera basin (San Juan, Cualcarnayo, Las Chacritas and Las Aguaditas Forrnations) are described. Two new genera, Cuyanella gen. nov. and Pseudoaechmina gen. nov., and eleven species have been recognized, four of which are new (Cuyanella argentina gen. et sp. nov., Eodominina ? longispina sp. nov., Pilla nodospinosa sp. nov. and Psendooeclnnina benedettoi gen. et sp. nov.). According to their stratigraphical distribution, two different ostracod associations have been identified. Association 1 occurs in the lower part of the Las Aguaditas Formation (P. tentaculatus Zone), Association II in the middle part (N. gracilis Zone). Association is correlated with the Las Chacritas Forrnation assernblage. Three of the eight genera described here are endemic, while Pilla and Eodominina are recorded for the first time outside Australia.